2005
DOI: 10.1007/11560548_20
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of SAT-Based Model Checking Techniques in an Industrial Environment

Abstract: Abstract. Model checking is a formal technique for automatically verifying that a finite-state model satisfies a temporal property. In model checking, generally Binary Decision Diagrams (BDDs) are used to efficiently encode the transition relation of the finite-state model. Recently model checking algorithms based on Boolean satisfiability (SAT) procedures have been developed to complement the traditional BDD-based model checking. These algorithms can be broadly classified into three categories: (1) bounded mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…This methodology is being introduced in validation methodology because not all the modules are well suited for simulations techniques. In [29], the authors presented the formal technique adopted by Brazil Semiconductor Technology Center (BSTC) which further divide into three additional techniques: model checking, theorem proving and equivalence checks. Model checking is an important technique for verifying sequential.…”
Section: Formal Verificationmentioning
confidence: 99%
“…This methodology is being introduced in validation methodology because not all the modules are well suited for simulations techniques. In [29], the authors presented the formal technique adopted by Brazil Semiconductor Technology Center (BSTC) which further divide into three additional techniques: model checking, theorem proving and equivalence checks. Model checking is an important technique for verifying sequential.…”
Section: Formal Verificationmentioning
confidence: 99%
“…These algorithms can be broadly classified into three categories: (1) bounded model checking which is useful for finding failures (2) hybrid algorithms that combine SAT and BDD based methods for unbounded model checking, and (3) purely SAT-based unbounded model checking algorithms. Studies in this direction was carried out by Amla et al [10] who have describes eight bounded and unbounded techniques, and analyzes the performance of these algorithms on a large and diverse set of hardware benchmarks. Most recently, Mancini et al [11] showed how by combining Explicit Model Checking techniques and simulation it is possible to carry effectively out (bounded) System Level Formal Verification of large Hybrid Systems such as those defined using model-based tools like Simulink.…”
Section: Related Work Of Model Checkingmentioning
confidence: 99%
“…Embedded memories give rise to an exponential increase in the state-space of a design, dramatically increasing the verification and debugging complexity of the system. This compounds the statespace explosion problem which already limits the practical application of many verification tools [2], [3].…”
Section: Introductionmentioning
confidence: 99%